Керамические клейма Булганакского городища - Храпунов, И.Н.; Федосеев, Н.Ф. (My University, 1997)
Chrapunov I. N., Fedoseev N. F. Ceramic Stamps of Bulganak Site of Ancient Settlement Bulganak site of ancient town is one of the biggest late-Scythian monuments. 48 ceramic stamps on the handles of hellinistic amphoraes were founded during the excavations of it Among them there're 20 from Rhodes, 5 from Cnidus, 11 from Chersonessus, 9 from Sinopa and 3 of unknown centres (look on the catalogue). The names of Sinopean magistrate Fainippou tou Pasicarou and potter Noumhnioz (Ns 40) on one stamp, were not found before. Our settlement achieved different goods in amphoraes almost uninterruptedly during III-II c. BC (Plate I). Chersonessus amphoraes appeared earlier, than others; then sinopean, Cnidus and Rhodes ones appeared. The finishing of Chersonessus stamps' deliveries concured chronologically with the destruction of many greek settlements in the North Black Sea Region at the end of the one third III c. BC and, evidently, with the beginning of the Scythian-Chersonessus wars. Comparing the Rhodes stamps from the Bulganak settlement and ones from the capital of Late-Scythians State Neapolis we can run to conclusion about high degree of similarity of this complexes. It's possible, that both this late-Scythian centres had close trade ties with Olbia in II c. BC.